THE EFFECT OF LEADERSHIP, MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN PRATAMA TAX SERVICE OFFICE IN SAWANGAN DEPOK - Junaidi, Ahmad; Affandi, Rusli; Wahyudin, Dian; As'ad; Badruddin, Syamsiah; Halim, Paisal (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research analyses employees' accomplishments by looking at some factors: Leadership, Motivation, and Job Satisfaction at the Sawangan Depok Pratama Tax Service Office (KPP), using the theory of [1] and [2] as the basis.This research is quantitative through questionnaires given at random to the KPP employees, executives in each section, account representatives, section heads, and functional examiners.The results show that leadership, motivation, and job content partially or jointly positively impact employee achievements by 65%. At the same time, other factors cause the remaining 35% called epsilon, namely work climate, culture work, external environment, work discipline, coordination, supervision, communication, incentives,planning, work ethic, employee capacity & competence, and facilities and infrastructure and so on.Among the three variables, the work motivation variable is the most significant influence on employee performance. Therefore, work motivation needs to be strengthened with continuous socialization and internalization to be maintained or improved to support employee performance and organizational goals, especially at the KPP.